Methodology for the exploration of coal bed methane (CBM) in Colombia coal basins - Mariño-Martínez, Jorge Eliecer; Mojica, Lucila (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2013)
It is ussually considered that commercial gas was only related to oil, but research has demonstrated that coal generates great volumes of methane and other gases (CBM). Colombia has big coal reserves, and it is expected that those coals contain enough CBM reserves that can be marketed inthe next years. This article presents the CBM methodologies used in the laboratory of materials, coal and gas, which is located in the UPTC-Sogamoso. The Colombian mining has traditionally presented the methane as a risk factor during the mining labors, but the gas explosions duo to methane has forced some to consider the CBM as an energy resource. Because of that interest, the main objective of this research has focused on adapting and establishing the methodologies and the procedures that should be used to determine the methane gas content by using desorption tests canisters. The canisters and theiradditional equipment have been adapted and improved in the UPTC by Geological Engineering research group during the last years. These CBM guides have been written following the current knowledge on CBM and propose additional recommendations for making the sampling and gas measuring more reliable and supportive of the CBM exploration projects that are taking place in the different coal basins in Colombia.